Villages in the Shadow of Village Administration: Local Wisdom Losing Its Role - Helmijar; Khairan; Arfriani Maifizar; Ikhsan Maifizar (Catalist Indo Publisher, 2026)
Background Mukim is a customary governance institution that holds a strategic position in Aceh’s local government system and functions as a guardian of local wisdom. However, in the context of contemporary village governance, its role has increasingly weakened. This study aims to examine the implementation of Mukim’s functions as a local wisdom institution and to analyze the structural constraints that limit its effectiveness in Teluk Dalam District, Simeulue Regency. Methods Employing a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving Imum Mukim, village heads, customary leaders, religious figures, community representatives, and local government officials. Data were analyzed using data reduction, display, and conclusion drawing techniques. Results The findings reveal that Mukim’s functions, as mandated by Simeulue Regency Qanun No. 5 of 2010, have not been optimally implemented. Mukim tends to operate symbolically and ceremonially, while its substantive roles in customary governance, development coordination, religious guidance, dispute resolution, and natural resource oversight remain marginal. The dominance of village government following the Village Fund policy has repositioned Mukim from an intermediate institution to a peripheral actor with limited authority. Using Robert K. Merton’s structural-functional perspective, the study identifies an imbalance between manifest and latent functions, resulting in institutional dysfunction. Conclusions The study concludes that strengthening Mukim requires not only normative recognition but also operational and structural reconstruction through clearer authority, capacity building, and institutional integration within local governance frameworks to restore its relevance as a living institution of local wisdom.